Menggali Strategi Manajemen Sumber Daya Manusia untuk Meningkatkan Keterlibatan Karyawan dan Kinerja Organisasi di Sektor Pendidikan - Rita Andini, Rita Andini; Nurdiyanto, Ahmad Dwi Nurdiyanto; Mohklas, Mohklas; Andini, Andini (ICON Publisher, 2025)
This study explores how human resource management (HRM) strategies influence employee engagement and organisational performance in educational institutions. Using a qualitative design involving in-depth interviews, document analysis, and field observation, the research examines how HRM practices are shaped by institutional culture, leadership behaviour, and emotional dynamics. Findings reveal that engagement emerges not from procedural control but from relational trust, inclusivity, and ethical leadership. The study identifies inclusive leadership, continuous professional development, transparent evaluation, and emotional intelligence as central mechanisms that strengthen motivation and institutional cohesion. Participants described that alignment between organisational values and HRM actions enhances legitimacy and reduces turnover intention. Conversely, inconsistency between moral discourse and managerial practice fosters disengagement. The study contributes theoretically by integrating ethical HRM and social exchange theory into a human-centred model of organisational sustainability. Practically, it offers insight into how educational leaders can cultivate engagement through fairness, empathy, and participative governance. The findings underscore the need for HRM frameworks that balance administrative efficiency with moral responsibility, ensuring long-term institutional resilience and professional fulfilment among educators.